1999
DOI: 10.1063/1.480485
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-body densities for the beryllium isoelectronic series

Abstract: One-and two-body densities in position space have been calculated for the atomic beryllium isoelectronic series starting from explicitly correlated multideterminant wave functions. The effects of electronic correlations have been systematically studied by comparing the correlated results with the corresponding Hartree-Fock ones. Some expectation values such as ͗␦(r)͘, ͗r n ͘, ͗␦(r 12 )͘, ͗r 12 n ͘, ͗␦(R)͘, and ͗R n ͘, where r, r 12 , and R stand for the electron-nucleus, interelectronic, and two electron cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…1͑a͒; ⌬H(u) is positive in the regions 0.50ϽuϽ1.09 and 3.44ϽuϽ7.87, whereas ⌬H(u) is negative mainly in the regions 0ϽuϽ0.50 and 1.09ϽuϽ3.44, where the symbol ⌬ stands for the correlated quantity subtracted by the corresponding Hartree-Fock quantity. Analogous correlation effects in ⌬H(u) were reported by Banyard et al 17,18 and by Gálvez et al, 21 but the first positive region is missing in the result of the latter authors.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…1͑a͒; ⌬H(u) is positive in the regions 0.50ϽuϽ1.09 and 3.44ϽuϽ7.87, whereas ⌬H(u) is negative mainly in the regions 0ϽuϽ0.50 and 1.09ϽuϽ3.44, where the symbol ⌬ stands for the correlated quantity subtracted by the corresponding Hartree-Fock quantity. Analogous correlation effects in ⌬H(u) were reported by Banyard et al 17,18 and by Gálvez et al, 21 but the first positive region is missing in the result of the latter authors.…”
Section: Resultssupporting
confidence: 62%
“…1͑b͒. Gálvez et al 21,23 reported similar behavior for ⌬D(R). The electron correlation in the Be atom reduces the average center-ofmass radius ͗R͘ of electron pairs.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations